Traverses of art and audience participation: An interview with Olaf Nicolai. Issue 181 (1st December 2016) - Irmer, Thomas
On the roof of the German pavilion at the 2015 Venice Biennale, Olaf Nikolai produced boomerangs whose shape was adapted to local wind currents. He thus reified the conditions of their production, while each thrower individualised each boomerang through their throwing. The art work was thus created only with the help of the participants; similarly to the installation with singers entitled Non Consumiamo... at the exhibition curated by Okwui Enwezor at the Arena.